Development and Application of Thermoregulatory Manikin: A Review (Journal of Fiber Bioengineering and Informatics, 2014)
Thermoregulatory manikin can simulate complex physiological human behaviors such as sweating,shivering and vasomotion which the human body uses in order to adapt to temperature changes inthe environment. Thus, it serves as a better simulation for human responses in the thermal environmentthan traditional ones. This paper first discusses the limitations of traditional manikins then followedby a summary of suitable thermal physiological models which have been implemented on manikins. Areview of the development and application of thermoregulatory manikin is made by comparing researchachievements of different research institutes. Currently, the thermal manikin system controlled bythermal physiological model has yet to be matured, which needs further validation before laboratoryapplications.